The Influence of the Learning System on Industrial Engineering Student Learning Motivation - Haniza, Haniza (PT FORMOSA CENDEKIA GLOBAL, 2024)
The learning system in higher education is the interaction of students with lecturers, education staff, fellow students, and other factors . Students in carrying out learning activities need certain encouragement so that their learning activities can produce learning achievements that are in line with the expected goals. Maximum student learning achievement certainly needs to take into account various factors that encourage students to study effectively. One of the causal factors that influences this is learning motivation. The motivation obtained by students will make them more responsible for their attitudes, both in the academic and social fields. The research objective of this study is to find out whether the Learning System has an effect on Learning Motivation and wants to know the magnitude of the direct and indirect influence of the Learning System on Learning Motivation. This research​ has 3 independent variables, namely Facilities, Environment and Learning Administration , 1 intervening variable namely Learning System and 1 dependent variable namely Learning Motivation. The results of this research are known to have a positive and significant effect. The most dominant variable in influencing learning motivation, where the learning system is the connecting variable, is the environmental variable of 5.763. The environment will have an impact on motivating students to study hard.